Biological activities of nerve growth factor bound to nitrocellulose paper by Western blotting - Pettmann, B (J Neurosci, 1988)
We have previously developed a cell-blot technique to visualize directly in tissue extracts molecules that display the biological activity of ciliary neuronotrophic factors (CNTFs). This technique involves SDS-PAGE of the tissue extract, Western blotting on nitrocellulose paper, neuronal cell culture on the paper, and, using a vital dye, visualization of the neurons that selectively survive on the trophic factor band. In this report, we show that (1) NGF, either purified or in a crude extract from submaxillary glands, can also be successfully recognized using a slightly modified cell-blot technique; (2) a variety of ganglionic neurons can respond to distinct nitrocellulose-anchored trophic factors; (3) while CNTF and NGF can both support the survival of their common target cells, only NGF also promotes neuritic extension; and (4) both the dimeric and the monomeric forms of immobilized beta-NGF are active.